Analisis risiko potensi bahaya dan pengendalian dengan metode HIRADC pada pabrik asam fosfat (Studi kasus: PT XYZ) - Ramadani, Deo Globy; Pulansari, Farida (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Occupational health and safety (OHS) in the phosphate acid plant industry is crucial due to the potential hazards from chemical substances and mechanical equipment. This study analyzes hazard identification, risk assessment, and control measures using the HIRADC method at PT XYZ. The results show that HIRADC effectively reduces risks from high to moderate or low categories. Key identified hazards include liquid spills, forklift-related risks, conveyor entrapment, ball mill noise, and phosphate rock dust exposure. Control measures implemented include regular cleaning, safety signage, personal protective equipment (PPE), and the LOTO system. This study recommends further research to enhance risk management effectiveness.